Local Women's Agency In Peace Building: A Study on the Conflict of Iron Sand Mining In East Java - Asnawan Asnawan (Ulumuna, 2018)
The local women as the agent in peace building are rare to be addressed in academic discourse. This paper seeks to analyse the roles played by local women in the conflict of iron sand mining in Wotgalih village, Lumajang regency, East Java Province. In the conflict situation, the women have already been as the backbone, carer and guard of the family replacing the roles of the men that do not function optimally. It is very clear how women played those roles by becoming farm laborers in watermelon field along Wotgalih Lumajang beach. In the post-conflict period, the women take an important role in fostering peace. They served as the spearhead for the reconciliation of the related parties.